Buddhist Ideologies from Dhamma Aphorisms in Monasteries in Chiang Mai, Thailand - Wongsi, Katbandit (Journal of Letters, 2018)
Aphorism signs found in Thai monasteries are a means of communication used by monks to relay the Buddha’s teaching (dhamma) to Thai Buddhists in general, and to share Buddhist ideologies. This study examines how Buddhist ideologies are constructed through these aphorisms. The analytical framework used is the discourse analysis approach of Teun Van Dijk (Van Dijk 1995a; 1995b; 1995c; 1998; 2006) and David Machin and Andrea Mayr (Machin and Mayr 2012). The results reveal that the constructed ideologies are based on the Noble Truths, proclaimed by the Buddha. They underlie Buddhist views on the nature of suffering, the causes of suffering, the annihilation of suffering and the practical ways to annihilate suffering. These ideologies aim to make Buddhists better understand the truth of life, and develop themselves to reach the ultimate goal of true happiness. They are constructed through five linguistic strategies: lexicalization, transitivity, speech acts, presupposition and metaphors.